The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s11292-009-9086-4
|View full text |Cite
|
Sign up to set email alerts
|

The DNA field experiment: a randomized trial of the cost-effectiveness of using DNA to solve property crimes

Abstract: We report the results of a prospective, randomized study of the impact and cost-effectiveness of DNA evidence in investigating property crimes, mainly residential burglary. Biological evidence was collected at up to 500 crime scenes in five U.S. cities between 2005 and 2007, and cases were randomly assigned to the treatment and control groups in equal numbers. DNA processing was added to traditional investigation in the treatment group. A suspect was identified in 31% of treatment cases and 13% of control case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 4 publications
2
51
0
1
Order By: Relevance
“…Peterson and colleagues () noted that “investigators [may be] more inclined to classify [stranger‐perpetrated] alleged sexual assaults as a crime (a requirement for uploading)” (p. 83). The CODIS entry and hit rates documented in this study were substantially higher than in other SAK‐related projects, but interestingly, they were similar to Roman, Reid, Chalfin, and Knight's () study of forensic testing outcomes for burglary crimes. In that project, DNA evidence from 1,079 burglary cases was tested, and 55% of the samples yielded a CODIS‐eligible profile, of which 43% produced a CODIS hit.…”
Section: Measuring Sak Testing Forensic Outcomes and The Use Of Forensupporting
confidence: 80%
“…Peterson and colleagues () noted that “investigators [may be] more inclined to classify [stranger‐perpetrated] alleged sexual assaults as a crime (a requirement for uploading)” (p. 83). The CODIS entry and hit rates documented in this study were substantially higher than in other SAK‐related projects, but interestingly, they were similar to Roman, Reid, Chalfin, and Knight's () study of forensic testing outcomes for burglary crimes. In that project, DNA evidence from 1,079 burglary cases was tested, and 55% of the samples yielded a CODIS‐eligible profile, of which 43% produced a CODIS hit.…”
Section: Measuring Sak Testing Forensic Outcomes and The Use Of Forensupporting
confidence: 80%
“…In Peterson and colleagues' (2012) in-depth examination of 1,320 SAKs randomly sampled from 10,895 "backlogged/untested" rape kits from Los Angeles that dated back to 1982, there were 699 DNA profiles entered into CODIS (53% of the total sample tested), resulting in 347 CODIS hits (26% of the total sample tested, 50% of profiles entered into CODIS; serial sexual assault rate not reported). These CODIS hits rates are similar to the results from an analysis of DNA forensic testing outcomes for 1,079 burglary cases from 2005 to 2007 (which were within SOL at the time the study was conducted), which found that 55% of the samples yielded a CODIS-eligible profile, of which 43% produced a CODIS hit (Roman, Reid, Chalfin, & Knight, 2009). Violent crimes against a person are markedly different from property crimes in many ways, and yet the DNA forensic testing outcomes across these studies were comparable: about half of the cases analyzed yielded CODISeligible profiles and then roughly 40% to 50% of those profiles produced CODIS hits.…”
Section: Prior Research On Sak Testing Forensic Outcomes and The Compsupporting
confidence: 74%
“…Only in 6% (176/2791) of HVC‐crime cases, DNA traces were actually analyzed. In a U.S. DNA field experiment on property crimes conducted in 2009 , a suspect was identified through a DNA database match in 16% of the cases. In 13% of the cases in the “DNA evidence group,” a suspect was identified through traditional police work.…”
Section: Conclusion and Discussionmentioning
confidence: 99%